A Case Report of Chordoma Presenting as a Sphenoid Sinus Mass: A Diagnostic Challenge - Bharti, Sushma; Bharti, Jyotsna N. (Current Medical Imaging, 2023)
Introduction: Chordomas are midline tumors that arise from remnants of the primitive notochord, while the heterotopic rests are usually situated extradural within the bones of the axial skeleton. The tumor is locally aggressive with a high recurrence rate but rarely gives rise to metastasis. Case Report: A 55-year-old female presented with complaints of headache and intermittent vomiting for six months and diminution of vision for the last four months. MRI, T1 weighted without contrast of the paranasal sinus, suggested sphenoid sinus malignancy or metastasis. The mass was excised and sent for histopathological examination. Based on the radiological findings, light microscopy, special stains, and immunohistochemistry, a final diagnosis of chordoma was rendered. Results: The chordoma is a well-known entity at the skull base. Skull-based chordomas account for only 0.1-0.2% of all chordomas. The incidence rate of chordomas is 0.08 per 100,000, with a higher incidence rate of 0.1 in males than in females. However, chordoma presenting as a sphenoidal mass will create a diagnostic challenge for all otorhinolaryngologists and head and neck surgeons. Conclusion: This case report aims to add this rare tumor to the differential diagnosis of neoplasms of the sphenoid sinus.
Keywords: Chordoma